2011
DOI: 10.1186/gm224
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs: a potential interface between the circadian clock and human health

Abstract: The biochemical activity of a stunning diversity of cell types and organ systems is shaped by a 24-hour (circadian) clock. This rhythmic drive to a good deal of the transcriptome (up to 15% of all coding genes) imparts circadian modulation over a wide range of physiological and behavioral processes (from cell division to cognition). Further, dysregulation of the clock has been implicated in the pathogenesis of a large and diverse array of disorders, such as hypertension, cancer and depression. Indeed, the poss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 85 publications
1
32
0
Order By: Relevance
“…Since it has been proposed that more than one third of human genes are regulated by miRNAs in diverse aspects of cell physiology [33, 34], and multiple miRNA species have been implicated in the molecular clock and output pathways in several model organisms [3541], it is highly likely that RNAi regulation plays critical roles in the mammalian clock. In an extensive in vivo study, Cheng et al implicated miR-219 and 132 in the time-keeping mechanism: brain-specific miRNA219 was implicated in period determination, while miRNA132 was implicated in photic entrainment [36].…”
Section: Introductionmentioning
confidence: 99%
“…Since it has been proposed that more than one third of human genes are regulated by miRNAs in diverse aspects of cell physiology [33, 34], and multiple miRNA species have been implicated in the molecular clock and output pathways in several model organisms [3541], it is highly likely that RNAi regulation plays critical roles in the mammalian clock. In an extensive in vivo study, Cheng et al implicated miR-219 and 132 in the time-keeping mechanism: brain-specific miRNA219 was implicated in period determination, while miRNA132 was implicated in photic entrainment [36].…”
Section: Introductionmentioning
confidence: 99%
“…Rhythmic control of microRNA expression appears to be highly conserved and has significant consequences for circadian timing [70]. As such several rhythmically regulated microRNAs were identified.…”
Section: Circadian Micrornasmentioning
confidence: 99%
“…This suggests that light might control these microRNAs. Within humans, it would not be surprising to observe a similar pattern of microRNA expression driven by exogenous time cues [70]. In fact, findings on miR-21 expression indicated regulation by light in mice and humans [19].…”
Section: Circadian Micrornasmentioning
confidence: 99%
“…In a very elegant study by the Obrietan laboratory [11,60], miR-132 was shown to mediate entrainment of the circadian clock in mice. In brief, the authors identified two miRNAs that are regulated by the circadian and light-induced transcription factor CREB: miR-132 and miR-219.…”
Section: Rspbroyalsocietypublishingorg Proc R Soc B 280: 20130011mentioning
confidence: 99%